2021
DOI: 10.1007/s10562-021-03818-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biofuel Additives from Glycerol Etherification Using Zirconia Supported Phosphotungstic Acid

Abstract: Using etherification to convert glycerol into biofuel additives is an effective way to solve the current problem of excess glycerol. In this study, a series of environmentally friendly (x)HPW/ZrO 2 catalysts were synthesized for the etherification of glycerol and tert-butyl alcohol (TBA). The internal microstructure and acidity analysis of the synthesized samples were derived from BET, XRD, Raman spectroscopy, FTIR, SEM, NH 3 -TPD and Py-FTIR. The results revealed that the synthesized catalysts retained the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The diffraction peaks of HPW were not observed in the HPW/ SnO 2 -ZrO 2 spectrograph, indicated that HPW is well dispersed on the surface of SnO 2 -ZrO 2 . [29] The diffraction peaks of HPW/TiO 2 -SnO 2 -ZrO 2 spectra appeared at about 2θ = 25.6°, 37.9°, 48.3°, 53.8°, 55.0°, 62.7° and 75.0°, these diffraction peaks were attributed to anatase TiO 2 . It has been proved that anatase titanium dioxide show high catalytic activity.…”
Section: X-ray Diffractionmentioning
confidence: 93%
See 1 more Smart Citation
“…The diffraction peaks of HPW were not observed in the HPW/ SnO 2 -ZrO 2 spectrograph, indicated that HPW is well dispersed on the surface of SnO 2 -ZrO 2 . [29] The diffraction peaks of HPW/TiO 2 -SnO 2 -ZrO 2 spectra appeared at about 2θ = 25.6°, 37.9°, 48.3°, 53.8°, 55.0°, 62.7° and 75.0°, these diffraction peaks were attributed to anatase TiO 2 . It has been proved that anatase titanium dioxide show high catalytic activity.…”
Section: X-ray Diffractionmentioning
confidence: 93%
“…These peaks are due to the interaction of pyridine with Brønsted(B) and Lewis(L) acid sites present on the catalyst surface. Liu et al [29] found that the parent ZrO 2 was mainly Lewis acid site and the total acid content was low by compared the Py-FTIR of HPW loaded with 0-15% ZrO 2 . With the increase of HPW loaded, the total acidity of the catalyst increased, especially the Brønsted acid.…”
Section: Py-ftirmentioning
confidence: 99%